Cross-species transmission of an ancient endogenous retrovirus and convergent co-option of its envelope gene in two mammalian orders. - J'Zaria Simpson; Christine A Kozak; Guney Boso (PLoS Genetics)
Endogenous retroviruses (ERVs) found in vertebrate genomes are remnants of retroviral invasions of their ancestral species. ERVs thus represent molecular fossil records of ancient retroviruses and provide a unique opportunity to study viral-host interactions, including cross-species transmissions, in deep time. While most ERVs contain the mutated remains of the original retrovirus, on rare occasions evolutionary selection pressures lead to the co-option/exaptation of ERV genes for a host function. Here, we report the identification of two ancient related non-orthologous ERV env genes, ARTenvV and CARenvV, that are preserved with large open reading frames (ORFs) in the mammalian orders Artiodactyla and Carnivora, respectively, but are not found in other mammals. These Env proteins lack a transmembrane motif, but phylogenetic analyses show strong sequence preservation and positive selection of the env surface ORF in their respective orders, and transcriptomic analyses show a broad tissue expression pattern for both ARTenvV and CARenvV, suggesting that these genes may be exapted for a host function. Multiple lines of evidence indicate that ARTenvV and CARenvV were derived from an ancient ancestral exogenous gamma-like retrovirus that was independently endogenized in two mammalian orders more than 60 million years ago, which roughly coincides with the K-Pg mass extinction event and subsequent mammalian diversification. Thus, these findings identify the oldest known retroviral cross-ordinal transmission of a gamma-like retrovirus with no known extant infectious counterpart in mammals, and the first discovery of the convergent co-option of an ERV gene derived from the same ancestral retrovirus in two different mammalian orders.